Physicochemical Properties of Avocado Seed Extract Model Beverages and Baked Products Incorporated with Avocado Seed Powder - Clinton O. Nyakang’i; Eunice Marete; Rebecca Ebere; Joshua M. Arimi (International Journal of Food Science, 2023)
Consumption of avocado (Persea americana Mill.) has increased worldwide in recent years. The avocado pulp is used, but the peel and seed are discarded as waste. Studies have shown that the seeds are rich in phytochemicals that can be utilized in food systems. The objective of this study was to evaluate the potential of Hass avocado seed as a source of polyphenols in the processing of model beverages and baked products with functional properties. The proximate analysis of the avocado seed powder was carried out. The shelf life of phenols in avocado seed powder (ASP) stored in dark, amber-colored bottle and transparent bottle was studied for six months. The seed extract was incorporated into model beverages of different pHs stored at refrigerated and ambient temperatures, and the shelf life was monitored for 20 weeks. The seed powder was incorporated into baked products at 0, 15, 30, or 50% followed by total phenolic content and sensory property analysis. Proximate composition of the seed powder for moisture, ash, protein, fiber, fat, and total carbohydrates was 14.19, 1.82, 7.05, 4.00, 13.64, and 59.30 percent, respectively. During storage of the seed powder, there was no significant difference (P>0.05) in the phenol content under the different storage light conditions for six months. In the model beverages, lower pH levels (2.8, 3.8, and 4.8) and those stored at ambient temperatures (25°C) recorded lower phenol content than the control pH, i.e., 5.5, and those under refrigerated conditions throughout the storage period studied (20 weeks). The concentration of phenols in the baked products increased with increasing avocado seed powder. The color of all the queen cake formulations was liked very much by the sensory panel. The aroma of 0% and 15% ASP was liked very much, while the other formulations (30% and 50%) were liked moderately. The taste rating and overall acceptability decreased with an increasing avocado seed powder in the queen cake formulations. Avocado seed extracts can be incorporated to prepare functional beverages and functional baked products that are acceptable by sensory panelists.